2021
DOI: 10.1177/08912432211029395
|View full text |Cite
|
Sign up to set email alerts
|

The Gendered Racialization of Asian Women as Villainous Temptresses

Abstract: What explains white male animus against Asian women? We address this question by examining the murders in Atlanta, GA, which reflect a larger global pattern of violence against what are perceived as hypersexualized Asian women. Dominant discourses on these murders promote either a narrative of racial xenophobia or a stance for or against sex work. Neither discourse adequately accounts for the simultaneous racial and gendered determination of Asian women’s experiences. In this commentary, we provide a racial–ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 7 publications
0
17
1
1
Order By: Relevance
“…We predicted that South Asian men would be perceived as more masculine and less feminine than East Asian men given the stereotypes of dangerous terrorists and facial features (darker phenotype, facial hair) that could hyper-masculinize South Asian men more so than East Asian men. We do not predict much difference between South and East Asian women in their perceived femininity-masculinity given that both groups are seen as particularly feminine and both Asian female groups are routinely objectified as exotic (Ahn et al, 2022;Hwang & Parreñas, 2021). As such, South and East Asian women may not reliably differ from one another.…”
Section: Current Researchmentioning
confidence: 62%
See 1 more Smart Citation
“…We predicted that South Asian men would be perceived as more masculine and less feminine than East Asian men given the stereotypes of dangerous terrorists and facial features (darker phenotype, facial hair) that could hyper-masculinize South Asian men more so than East Asian men. We do not predict much difference between South and East Asian women in their perceived femininity-masculinity given that both groups are seen as particularly feminine and both Asian female groups are routinely objectified as exotic (Ahn et al, 2022;Hwang & Parreñas, 2021). As such, South and East Asian women may not reliably differ from one another.…”
Section: Current Researchmentioning
confidence: 62%
“…Racial stereotypes are gendered such that Asian Americans are stereotypically considered as more feminine than Black and White people (Galinsky et al, 2013;Johnson et al, 2012;Wilkins et al, 2011). In the United States, Asian women are seen as exotic and objects of sexual desires (Hwang & Parreñas, 2021) and Asian men are seen as effeminate and asexual (Iwamoto & Kaya, 2016). As such, the larger Asian American group is seen as more feminine than other racial groups.…”
Section: Gendered Perceptions Of East and South Asian Facesmentioning
confidence: 99%
“…However, some studies have found no gender differences in loss of employment rates during COVID-19 [ 30 ], or levels of psychological distress across all Asian subgroups [ 66 ]. We still encourage future research to include gender as a potential factor of difference in experiences, particularly because of the intersectionality of being Asian/Asian American and a woman often means hyper-sexualization and violence (e.g., the Atlanta spa shootings in 2021) [ 67 ]. Additionally, the evidence for gender disparities in mental and physical health as well as economic status is well documented [ 67 – 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the need to understand the murders of Asian/American massage workers in Atlanta in 2021 motivated this special issue, to our great disappointment we did not receive any submissions on the experiences of violence by Asian/American women-despite Crenshaw's (1991) foregrounding not only Black women's but also Asian/American women's experiences of gendered violence in her formulation of intersectionality. Hwang and Parreñas (2021) remind us of the pressing need to address Asian/American women's epistemic absence in our analysis of racialized and gendered violence. As they argue, the murders in Atlanta resulted from Asian/American women's hypersexualization in cinema and the law as villainous temptresses.…”
Section: Recentering Women Of Color In Intersectional Analysismentioning
confidence: 99%